Perbedaan Tekanan Darah Pasca Anestesi Spinal Dengan Pemberian Preload Dan Tanpa Preload Ringer Laktat - Nabhani Nabhani; Muhammad Hafiddudin; Aka Amri Febri Atmoko (Pusat Riset dan Inovasi Nasional, 2021)
One way to prevent the decrease in blood pressure is by giving preload. To examine the difference in blood pressure after spinal anesthesia with Ringer's lactate preload and without preload. The design of this research is descriptive experimental with cross sectional. The sample consisted of 30 patients who will undergo spinal anesthesia at the Central Surgical Installation of RSUD dr. H. Jusuf SK Tarakan who has met the research criteria. Patients were divided into 2 groups, group 1 received Ringer's lactate preload and group 2 did not receive preload. Blood pressure checks include systolic blood pressure and diastolic blood pressure before spinal anesthesia and immediately after spinal anesthesia every 5 minutes to 30 minutes. The hypothesis test used is the paired t-test. The value of p = 0.05 was declared significant. There was a significant difference between blood pressure before being given preload and blood pressure after being given preload at 15-30 minutes hemodynamics (p=0.0001)